KINEMATIC AND ACOUSTIC OPTIMIZATION OF CAMERA AND AUDIO RECORDING SYSTEMS FOR ENHANCED MEDIA PRODUCTION — REVIEW - Kale, Shantanu; R. Deore, Narendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The convergence of camera kinematics and acoustic optimization has emerged as a crucial frontier in media production. Traditionally, cinematography and audio engineering have been treated as parallel but independent workflows, often resulting in trade-offs between visual framing and sound fidelity. This review synthesizes advances in kinematic modeling, trajectory planning, stabilization systems, and learning-based cinematography alongside parallel developments in microphone directivity, beamforming, room acoustics, and adaptive noise control. By examining these domains jointly, we highlight how multi-objective formulations and Pareto-front trade-offs can guide camera placement, path planning, and acoustic treatment to maximize perceptual quality of experience (QoE) for audiences. Special emphasis is placed on audiovisual alignment, motor noise mitigation, and the role of on-set compute for real-time optimization in broadcast, film, virtual reality, and live event contexts. The paper also reviews key datasets, simulators, and open-source tools that support benchmarking, reproducibility, and system integration. Contributions of this work include mapping the foundations of joint kinematic–acoustic design, identifying gaps in metrics and evaluation, and providing guidelines for future research and deployment. The review serves as a resource for academics, engineers, and creative professionals seeking to advance immersive media production.